(untitled) (Kronika Bydgoska, 2014)
The issue related to martial law and the campaign of detaining anticommunist activists carried out at that time in the Bydgoszcz Province was a topic of several scientific publications, in which the main attention was focused - which is understandable - on the victims of activities of the Security Service and determination of the scale of repressions used by the communist authorities. In order to expand the existing perspective of research, the authors of the article took a closer look on of the main coordinators and those who performed a wave of arrests which took place on the night between December 12 and 13, 1981. The finding of a previously unknown study entitled “Detaining Institution Under Martial Law” of Lt Col Stefan Witkowski, head of the Investigation Department of the Citizens’ Militia Regional Headquarters in Bydgoszcz, written in 1985, gave rise to a prosopographical analysis of the investigating officers of the Bydgoszcz Security Service. This document unveils opinions and concepts of a high ranking officer of the Security Service on detaining opposition activists, which were supposed to help in drawing conclusions allowing to amend the departmental regulations on state of emergency and to avoid in the future errors and negligence by officers of security and public order of the Polish People’s Republic under martial law.